2015
DOI: 10.1016/j.brainres.2014.10.048
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging biomedical informatics for assessing plasticity and repair in primate spinal cord injury

Abstract: Recent preclinical advances highlight the therapeutic potential of treatments aimed at boosting regeneration and plasticity of spinal circuitry damaged by spinal cord injury (SCI). With several promising candidates being considered for translation into clinical trials, the SCI community has called for a non-human primate model as a crucial validation step to test efficacy and validity of these therapies prior to human testing. The present paper reviews the previous and ongoing efforts of the California Spinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 88 publications
0
15
0
Order By: Relevance
“…cyst formation) [56], cortical reorganization [31] and the inherent low capacity of repair [57]. In particular, rodent and primate models of SCI have demonstrated progressive axonal anterograde and retrograde degeneration of spinal pathways with subsequent neuronal changes at multiple levels [58][59][60].…”
Section: Animal Models Of Spinal Cord Injury: Invasive Tracking Of Trmentioning
confidence: 99%
“…cyst formation) [56], cortical reorganization [31] and the inherent low capacity of repair [57]. In particular, rodent and primate models of SCI have demonstrated progressive axonal anterograde and retrograde degeneration of spinal pathways with subsequent neuronal changes at multiple levels [58][59][60].…”
Section: Animal Models Of Spinal Cord Injury: Invasive Tracking Of Trmentioning
confidence: 99%
“…These models represent important tools for continued progress in translational research and include injuries to the spinal cord in rhesus macaques at the cervical (Rosenzweig et al, ; Nout et al, 2012b), thoracic (Courtine et al, ) and lumbosacral levels (Ohlsson et al, ). Comprehensive and clinically relevant outcome measures allow for the evaluation of spontaneous plasticity of spinal cord circuitries and for preclinical testing of new treatment strategies in these nonhuman primate models (Nout et al, 2012a; Nielson et al, ).…”
mentioning
confidence: 99%
“…Regardless of the line of thought, there must be coordination between the forelimbs and hind limbs (Cazalets & Butrand, 2000;Nathan, Smith & Deacor, 1996), as well as memorization of this coordination (Nielsen, et al, 2015;Zhong et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated how repeated rehabilitation exercises that stimulate the afferent and efferent sensory-motor pathways allow the spinal neural circuits to memorize the rehabilitation exercises which were practiced, and thus the neurorehabilitation will depend on repetition and qua-lity of the locomotor training (Nielsen et al, 2015;Zhong et al, 2012).…”
Section: Neural Plasticity In Human Biped and Quadruped Animalmentioning
confidence: 99%